UTILIZATION OF CLASSIFICATION AND SHELVING SYSTEMS FOR INFORMATION RETRIEVAL IN THE INSTIDLA LIBRARY - Mubarok, Rahman; Satria, Abadi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This article investigates the classification and shelving systems at the INSTIDLA library and their impact on information retrieval. The study employs a qualitative descriptive research design, utilizing primary and secondary data sources to analyze the library's management and organization of collections . The research focuses on the implementation of the Dewey Decimal Classification system and the arrangement of materials in alphabetical order for shelving, as well as the challenges and deficiencies encountered in the classification and shelving system . The findings reveal that while the classification and shelving systems at INSTIDLA play a significant role in facilitating information retrieval, there are challenges such as the absence of dedicated staff for organizing books and the occasional lack of awareness among librarians about collection arrangement . The article concludes by proposing potential solutions to enhance the effectiveness of information retrieval at INSTIDLA.